The effect of vapour formation and metal droplet temperature and mass on vapour explosion behaviour. (1st November 2022) - Simons, A.; Bellemans, I.; Crivits, T.; Verbeken, K.
Highlights: Higher melt mass results in higher vapour explosion probability. Higher melt mass did not affect the vapour explosion intensity. Increasing melt temperature caused a higher explosion depth and intensity. The temperature had varying effects in combination with gas column aspect ratio ARgas . At low/high temperature, probability and intensity de-/increased with reducing ARgas . Abstract: Vapour explosions are a known hazard in pyrometallurgy that can cause equipment damage, injuries or even casualties. Therefore, molten metal droplet impingement experiments (2.5–20 g) with low-melting metals (Hg, Sn) were performed to study the vapour explosion phenomenon more thoroughly. A hydrophone and a high-speed camera continuously monitored these experiments. The influence of temperature and mass on the resulting interaction was investigated. Specific attention was given to the reproducibility of the experiments, most certainly in case the droplet fragmented into multiple droplets before entering the water bath. Mercury at room temperature was used to study the fragmentation step upon alloy-water impact without vapour formation. Air was seen to be dragged into the water as a column, where the observed aspect ratio of the gas columns decreased, i.e. the columns became longer, when the vertical length of the droplets was elongated. Molten tin (350–800 °C) was used to study the influence of vapour formation on fragmentation, and the effect of the hot phase mass and temperature on the explosion. The gas column occurrence frequency increased as compared to mercury experiments, and such gas column could potentially inhibit vapour explosions. Furthermore, an increased temperature resulted in an increased explosion probability, explosion energy, and depth of the spontaneous interaction. Lastly, increasing the melt mass resulted in an increased explosion probability and intensity. Graphical abstract: Image, graphical abstract